Von der Naturanlage zur Spitzenleistung : Eine Studie zu Pindars Menschenbild - Vogel, Christian (Untersuchungen zur antiken Literatur und Geschichte ;, 2019)
How much credit does Pindar give to people for their successes in his victory poems? This book investigates how factors such as talent, learning ability, personal attitude, and the divine help inform Pindar's view of humanity. The comparison with Aristotle's writings here is particularly illuminating, because it explains Pindar's underlying work ethic and reveals him to be a surprisingly modern poet.